The Correlation of Liquefaction Potential and Probability on Excess Pore Water Pressure in Kretek 2 Bridge Area - Zakariya, Ali; Rifa'i, Ahmad; Ismanti, Sito (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2024)
Liquefaction is soil condition associated with the drastic increase in pore water pressure of uniform sandy soil due to an enormous earthquake. Therefore, this study aimed to investigate the correlation of liquefaction potential with excess pore water pressure ratio in nine boreholes located at Kretek 2 Bridge area using empirical and numerical methods. Liquefaction potential was estimated based on a semi-empirical method simplified by Idriss and Boulanger (2008), and safety factor (SF) value of <1.0 was used to represent the existence of its potential. The result showed that liquefaction potential was dominant at depths of 1.5 to 6.0 m, with the exception of BH-9 with 16.5 m and BH-4. Furthermore, the excess pore water pressure ratio was estimated using empirical method developed by Yegian and Vitelli (1981) as well as Serafini and Perlea (2010). Numerical analysis was also conducted for comparison purposes and the process focused on using Deepsoil v7.0 to generate excess pore water pressure by considering soil conditions and dominant seismic sources in Kretek 2 Bridge area. The result showed that the ratio of excess pore water pressure was greater or equaled 0.8. Both empirical and numerical methods produced similar values for BH-1, BH-2, BH-8, and BH-9 at a depth of 1.5–3.0 m, 3–4.5 m, 3.0 m, and 16.5 m, respectively. This showed a correlation between excess pore water pressure ratio and liquefaction potential values at the same depth. However, numerical method tended to overestimate the ru value, necessitating the use of empirical method to obtain a more reliable result.